Effect of arginine and threonine administered in ovo on digestive organ developments and subsequent growth performance of broiler chickens. Issue 5 (26th November 2015) - Tahmasebi, S.; Toghyani, M.
Summary: This trial was conducted to investigate the effect of arginine (Arg), threonine (Thr) and Arg + Thr administered in ovo on growth performance, digestive organs and intestinal morphology in broiler chickens. On day 14 of incubation, 400 fertile eggs were randomly allotted to five experimental treatments through injection in the amniotic fluid including: (i) control (none injected), (ii) sham (0.5 ml of 0.5% saline), (iii) Arg (35 mg/egg), (iv) Thr (25 mg/egg) and (v) Arg + Thr (35 + 25 mg/egg). After hatching, chicks were given a commercial corn–soya bean diet up to 42 days of age. Daily feed intake (FI) and body weight (BW) of chicks were measured during different periods of the trial. Digestive organs were measured for their relative weight and intestinal length on days 11 and 42 of age. Intestinal morphometric traits were evaluated on day 11 of the experiment. Supplementing amino acids affected the performance of broiler chicks as Thr significantly increased FI and BW across starter, grower and finisher periods compared with sham and control (p   <   0.05). Furthermore, Arg + Thr injection increased jejunal weight compared with control on day 42 (p   <   0.05). Moreover, Arg inclusion led to the greatest villus height and crypt depth among treatments in duodenum (p > 0.05); however, amino acid supplemented groups had lower villus height than control in jejunum (p   <   0.05). Negative correlations found between digestive organs related to day 11 of age containing pancreas ( r  = −0.484; p = 0.030), duodenal ( r  = −0.577; p   =   0.007) as well as ileal lengths ( r  = −0.471; p   =   0.035) and FI of entire period. Otherwise, positive relationships were observed between duodenum ( r  = 0.580; p   =   0.007) and ileum ( r  = 0.582; p   =   0.007) weights on day 42 and FI of chickens across the entire phase. In conclusion, Arg and particularly Thr injection into amnion can improve FI and post‐hatch growth performance of chickens which may be mediated by the development of digestive organs.